Melatih Kataloger di Era Teknologi Informasi - Himayah, Himayah (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2014)
On-the-job training is needed in various scenarios and takes on a number of different guises. Each institution has its own unique, evolving needs that will are ongoing staff training. New employees, even when they are experienced lagers, undoubtedly will need to learn about local cataloging rules, work flow and possibly the library management system. A new job might also involve cataloging new types of material. On-the-job training is particularly vital for library school graduates as they face additional issues concerning practical application of their cataloging education. Every library staf needing cataloging training will be a professional librarian, and it is also required for paraprofessionals who perform cataloging tasks. Determining the objectives of the training should always be the first step, and these objectives will inform the whole planning process. While some training ideas are as important now as they were 20 years ago, the twenty’-first-century library brings new challenges. For instance, the changes in library school curricula mean that traditional assumptions about a new graduate’s cataloging skills must be discarded. However, twenty-first-century cataloging training is not just situated in the present and future; to fully understand present-day cataloging and cataloging rules, trainees need to understand past practices of retrieval and to reimagine its card catalog roots. Therefore, twenty-first-century libraries need an army of Janus-like catalogers where each one trains their recruits to look to the past, present, and future.